PENGEMBANGAN KOMIK BUDAYA ”TONḌU’ MAJÂNG” SEBAGAI MEDIA PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Amalia, Riska; Sari, Tita Tanjung; Kadarisman, Kadarisman (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
Cultural comics are one of the alternative reading materials to increase students' knowledge of learning related to the socio-cultural environment in the neighborhood. This study aims to develop media in the form of cultural comics